Microbiome dynamic: diversity in healthy and mastitis milk herd - Tan, Y. J.; Koh, S. P.; Khozirah, S.; Rozaihan, M.; Jacob, M.; Khirrol, N. A.W.; Mohd-Shaharizan, M. S.; Tan, G. H. (Bogor Agricultural University, 2025)
Bovine mastitis is the inflammation of udder due to physical injury or microbial infections. The milk from different mastitis statuses present different microbial profiles that can impact the mechanisms and pathophysiology of mastitis. An increasing number of studies provided evidence indicating the occurrence of dysbiosis in the microbiota during clinical mastitis. Our study aimed to investigate the shifts in mastitis milk microbiota over a three-week period within a Jersey Friesian mastitis herd in a local farm (n=20). The milk samples were collected from healthy animals (HT), clinical mastitis milk at different time frames throughout three weeks (W1, W2, and W3) (n=5). Microbial genomic DNA from milk samples was extracted and then submitted for 16S amplicon sequencing. The 16S amplicon sequencing analysis revealed that the predominant phyla in the core microbiota were Firmicutes, Actinobacteriota, Proteobacteria, and Bacteroidota. Alpha diversity indicated the presence of lower bacterial diversity in the clinical mastitis group across the weeks (W1, W2, W3) in comparison to the healthy (HT) group. Among the four dominant phyla, Firmicutes exhibited the highest percentage of abundancy (HT=35.40%; W1=63.10%; W2=89.32%; W3=90.86%), followed by Actinobacteriota (HT=34.08%; W1=7.87%; W2=1.01%; W3=6.95%), Proteobacteria (HT=11.17%; W1=18.69%; W2=7.50%; W3=1.14%), and Bacteroidota (HT=14.77%; W1=1.86%; W2=1.01%; W3=0.88%). The diversity indices exhibited a decreasing trend from W1 to W3 (Chao1 index: HT=323, W1=297, W2=69, W3=35; Shannon index: HT=3.41, W1=3.87, W2=1.50, W3=0.92). Beta diversity displayed a scattered pattern of sample clustering in PCA plots among different groups. In conclusion, the dominance of Firmicutes persisted throughout the weeks, while other populations decreased over the specified time frame. The healthy (HT) group maintained a more diverse distribution of phyla.